Resilient Apartheid survivors and their navigation of historical trauma at the Castle of Good Hope, Cape Town - Johannes, Shanél (Department of Political Studies, 2021)
The history of South Africa entails colonial and apartheid era violence and trauma (visible and invisible) which ingrained various socio-economic-political-agrarian orders of brutalisation, mass killings, and the displacement of local people from their culture, language, land, agency, and spirituality. Attached to such history, are the intact remnants of the colonial and apartheid eras – national heritage monuments. The Castle of Good Hope, as a national heritage site, is not limited as being the oldest architectural structure in Cape Town, nor is it only a transitioning site that tries to incorporate democratic principles of multiple heritage. This site wields memories of both individual and collective historical colonial and apartheid trauma. Critically, this research project seeks to empirically analyse whether historical traumas are embedded in the displaced landscape and individual and collective experiences as the descendants of the colonised, enslaved, and oppressed. Historical trauma in this context, is often associated with the scholarship on the trans-Atlantic slave trade (from Africa to the Americas). However, little work is done in relation to the descendant's navigation of trauma – the resultant of the Indian Ocean trade and slave trade. The trauma related to the violent occupation of the European nations, transcended itself and was continued through various apartheid policies which has prevailing legacies of intergenerational historical trauma in Cape Town. Thus, this qualitative empirical research project seeks to explore the memories, experiences, and recommendations of resilient apartheid survivors – the descendants of the colonised, enslaved, and oppressed generations – and the ways in which they navigate the Castle of Good Hope as a site of historical trauma.